2022
DOI: 10.3390/su142416854
|View full text |Cite
|
Sign up to set email alerts
|

Soil Heterogeneity Effects on Bridge Piles Deformation under Shield Tunnelling Disturbance

Abstract: This research examines the impact of soil heterogeneity on the bridge piles beneath a nearby tunnel excavation using Monte-Carlo stochastic analysis. Sensitivity analysis is specifically used to the variation of stratum range, variation coefficient (COV), and fluctuation distance of the soil Young’s modulus. Meanwhile, the reliability evaluation approach is also applied to systematically examine the impact of COV on the likelihood of a pile failing. The findings suggest that more consideration should be given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Due to its calcium sulfate nature, PG serves as a replacement for natural gypsum in the manufacturing of cement, wallboard, road base and pavement material, ferrocement panels, plasterboard panels, partition blocks, plaster, artificial stone, glass ceramics, and various other building materials [103][104][105]. Using PG in construction materials instead of natural gypsum offers numerous potential advantages.…”
Section: Construction and Building Materialsmentioning
confidence: 99%
“…Due to its calcium sulfate nature, PG serves as a replacement for natural gypsum in the manufacturing of cement, wallboard, road base and pavement material, ferrocement panels, plasterboard panels, partition blocks, plaster, artificial stone, glass ceramics, and various other building materials [103][104][105]. Using PG in construction materials instead of natural gypsum offers numerous potential advantages.…”
Section: Construction and Building Materialsmentioning
confidence: 99%
“…Numerous engineering examples have shown that the stability of drilled-shaft walls is influenced by various factors, with mud slurry protection playing a vital role [4]. Scholars have conducted theoretical analysis [5,6], laboratory experiments [7][8][9][10][11], field experiments [12][13][14], and numerical simulations [15][16][17][18] to study the issue of mud slurry protection and soil stability. The unreinforced and geogrid-reinforced soil foundations were modeled using a particle flow code of two dimensions (PFC2D) and the effects of four different factors on footing settlement were investigated [19].…”
Section: Introductionmentioning
confidence: 99%
“…* email: 1726773845@qq.com; wushengzhi19@sdjzu.edu.cn www.nature.com/scientificreports/ through numerical simulation, and evaluated the reliability of the reinforcement measures. Basile and Loganathan et al [20][21][22][23] evaluated the influence of tunnel excavation, tunnel depth, and soil inhomogeneity on existing pile foundations and provided reasonable pile-response predictions for many practical situations 24 . Chen 25 and Wang 26 studied the influence of different construction sequences on existing piles, and proposed a new construction method, i.e., the tunnel-column method 27 .…”
mentioning
confidence: 99%